Atmospheric circulation simulations in the present and Future climate associated with temperature drop in Southeastern south America - Cintia Rabelo da Rocha Repinaldo; Gabriela Viviana Müller; Kelen Martins Andrade (Boletín Geográfico)
The atmospheric features associated with extreme cold events, identified by the temperature drop in the winter, in three regions of southeastern South America are analyzed with reanalysis data from NCEP / NCAR as well as simulations of the coupled ocean-atmosphere HadCM3 and GFDL-CM2.0 models for the present and CMIP3 A2 future scenario. In the present climate, GFDL-CM2.0 represents better the reanalysis fields, being more coherent with the post-frontal high pressure and the 0°C and better the reanalysis fields, being more coherent with the post-frontal high pressure and the 0°C and10°C isotherms. For the future climate, GFDL-CM2.0 projects weakening of temperature anomalies and lower advance of the extreme events of temperature drop in direction to the Equator, while the HadCM3 projection also indicates lower latitudinal range, but in general, higher intensity of these events.